2022
DOI: 10.3390/polym14061207
|View full text |Cite
|
Sign up to set email alerts
|

Employing Cellulose Nanofiber-Based Hydrogels for Burn Dressing

Abstract: The aim of this research was to fabricate a burn dressing in the form of hydrogel films constructed with cellulose nanofibers (CNF) that has pain-relieving properties, in addition to wound healing. In this study, the hydrogels were prepared in the form of film. For this, CNF at weight ratios of 1, 2, and 3 wt.%, 1 wt.% of hydroxyethyl cellulose (HEC), and citric acid (CA) crosslinker with 10 and 20 wt.% were used. FE-SEM analysis showed that the structure of the CNF was preserved after hydrogel preparation. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Basti et al showed that hydrogels constructed from hydroxyethyl cellulose and citric acid crosslinker were non-toxic to NIH-3T3 cells after 1 and 3 days of exposure. 63 Similar results were obtained by Ezati et al, who showed that functional CNF-based films prepared by incorporating two types of carbon dots were non-toxic to L929 cells after 72 h treatment. 64 The results from these studies suggest that even if CNFs are in contact with a larger area of the cell, the effect on cell viability is limited.…”
Section: Discussionsupporting
confidence: 86%
“…Basti et al showed that hydrogels constructed from hydroxyethyl cellulose and citric acid crosslinker were non-toxic to NIH-3T3 cells after 1 and 3 days of exposure. 63 Similar results were obtained by Ezati et al, who showed that functional CNF-based films prepared by incorporating two types of carbon dots were non-toxic to L929 cells after 72 h treatment. 64 The results from these studies suggest that even if CNFs are in contact with a larger area of the cell, the effect on cell viability is limited.…”
Section: Discussionsupporting
confidence: 86%
“…The research using hydrogel as a scaffold for tumor cell pyroptosis opens up a new perspective. Scientists reported the superiority of cellulose nanofiber-based hydrogels as a release drug stent ( 97 , 98 ). Another paper also pointed out the feasibility of embedding 5-FU on pyroptosis induction in cellulose nanofiber-based hydrogels ( 99 ).…”
Section: Strategies Of Pyroptosis In Cancer Therapymentioning
confidence: 99%
“…Such modified cellulose-based biomaterials offer large advantages over known conventional ones and show great promise in medical applications. Due to cellulose’s biodegradable and non-toxicity properties, its biocompatibility and its hydrophilicity, it has been widely used as dressings for difficult-to-heal wounds, tissue engineering scaffolds or controllable drug delivery systems [ 16 , 28 , 29 ]. Reducing the size of cellulose particles is one of the ways of modifying their physicochemical parameters.…”
Section: Introductionmentioning
confidence: 99%